4040 SNPs for genomic analysis in the rhesus macaque (Macaca mulatta) - Trask, J Satkoski (2011)
Although the rhesus macaque (Macaca mulatta) is commonly used for biomedical research and becoming a preferred model for translational medicine, quantification of genome-wide variation has been slow to follow the publication of the genome in 2007. Here we report the properties of 4040 single nucleotide polymorphisms discovered and validated in Chinese and Indian rhesus macaques from captive breeding colonies in the United States. Frequency-matched measures of linkage disequilibrium were much greater in the Indian sample. Although the majority of polymorphisms were shared between the two populations, rare alleles were over twice as common in the Chinese sample. Indian rhesus had higher rates of heterozygosity, as well as previously undetected substructure, potentially due to admixture from Burma in wild populations and demographic events post-captivity.